Distinct effects of ubiquitin overexpression on NMJ structure and motor performance in mice expressing catalytically inactive USP14 - Vaden, Jada H.; Watson, Jennifer A.; Howard, Alan D.; Chen, Ping-Chung; Wilson, Julie A.; Wilson, Scott M. (Frontiers in Molecular Neuroscience, 2015)
Ubiquitin-specific protease 14 (USP14) is a major deubiquitinating enzyme and a key determinant of neuromuscular junction (NMJ) structure and function. We have previously reported dramatic ubiquitin depletion in the nervous systems of the USP14-deficient ataxia (axJ) mice and demonstrated that transgenic ubiquitin overexpression partially rescues the axJ neuromuscular phenotype. However, later work has shown that ubiquitin overexpression does not correct the axJ deficits in hippocampal short term plasticity, and that transgenic expression of a catalytically-inactive form of USP14 in the nervous system mimics the neuromuscular phenotype observed in the axJ mice, but causes a only a modest reduction of free ubiquitin. Instead, increased ubiquitin conjugates and aberrant activation of pJNK are observed in the nervous systems of the USP14 catalytic mutant mice. In this report, we demonstrate that restoring free ubiquitin levels in the USP14 catalytic mutant mice improved NMJ structure and reduced pJNK accumulation in motor neuron terminals, but had a negative impact on measures of NMJ function, such as motor performance and muscle development. Transgenic expression of ubiquitin had a dose-dependent effect on NMJ function in wild type mice: moderate levels of overexpression improved NMJ function while more robust ubiquitin overexpression reduced muscle development and motor coordination. Combined, these results suggest that maintenance of free ubiquitin levels by USP14 contributes to NMJ structure, but that USP14 regulates NMJ function through a separate pathway.